The Identification of Classroom Physical Environmental for Wheelchair Users in Inclusive Schools - Dwi Arnia Ulfa (Indonesian Journal of Disability Studies, 2018)
This study aims to determine the classroom physical environment of wheelchair users in inclusive schools. This research was conducted in two inclusion schools in Surakarta City. This study used descriptive qualitative method. Data collection is done by interview, observation and documentation. The results showed that some of the things that teachers have done related classroom arrange for wheelchair users are an easy door for wheelchair users, non-slip floors, seating is easy to reach by students, provided ventilation and light enough, and available device have been modified. While the obstacles experienced by wheelchair users are the distance between the table is difficult to pass the wheelchair, difficulty in using modified device, difficulty move in building multi-storey school building and path to a class that has not been smooth.